Investigaciones histórico-médicas sobre salud y enfermedad en el pasado. Actas del IX Congreso Nacional de Paleopatología - Rocha, Leonor (2010)
This is the result of the study of the human osteological remains proceeding from the interventions of prof. Manuel Heleno on megalithic monuments of the Central Alentejo, and deposited in the collections of the MNA. In scientific terms, these information is of great importance,taking in account the fact that schist and granit soils - where the most of the monuments are located - make difficult the preservation of this kind of evidence.